BLR Size in Realistic FRADO Model: The Role of Shielding Effect - Naddaf, Mohammad-Hassan; Czerny, Bożena; Szczerba, Ryszard (Frontiers in Astronomy and Space Sciences, 2020)
The effective size of broad line region (BLR), so-called the BLR radius, in galaxies with active galactic nuclei (AGN) scales with the source luminosity. Therefore, by determining this location either observationally through reverberation mapping or theoretically, one can use AGNs as an interesting laboratory to test cosmological models. In this article we focus on the theoretical side of BLR based on the Failed Radiatively Accelerated Dusty Outflow (FRADO) model. By simulating the dynamics of matter in BLR through a realistic model of radiation of accretion disk (AD) including the shielding effect, as well as incorporating the proper values of dust opacities, we investigate how the radial extension and geometrical height of the BLR depends on the Eddington ratio [and blackhole mass], and modeling of shielding effect. We show that assuming a range of Eddington ratios and shielding we are able to explain the time-delays in a sample of reverberation-measured AGNs.